THE SOCIO-PRAGMATIC FUNCTION OF IRONY ON SOCIAL MEDIA: Using examples from Johan Deckman’s art pictures on Instagram - Nikabadze, Mari (Online Journal of Humanities ETAGTSU, 2024)
Irony conveys a tinge of derogation, criticism, and contempt in an attitude, meaning the opposite of what has been said (Grice, 1967). This paper deals with the socio-pragmatic perspective of irony on social media (Instagram), investigating the following issues: 1. Why would a speaker decide to be ironic, and how is irony encoded in their utterance? 2. How can readers grasp ironic intentions in the examples of the studied Instagram account? 3. Despite being negative, can irony serve a positive social function? On that account, we shall try to analyze Johan Deckman’s art displayed in photos on his Instagram account. The scope of the creator’s intentions and the contents of his utterances will also be inspected. Moreover, this paper studies readers’ decoding of irony by analyzing the comment section. From a pragmatic perspective, this research will be carried out through the following components: 1. background knowledge of the creator/reader and their general perception of the world (Colston & Katz, 2005); 2. the situational character of irony (Kotthoff, 2003); 3. the allusional pretense in irony (Kumon-Nakamura et al., 1995). From a functional perspective, the study is based on the following categories of irony employment: 1. Humor 2. The elevation of the social status 3. Aggression 4. Emotional control (Dews et al., 2009). Based on the researched data, this article also suggests a hypothesis that there is one more category to add to those offered by Dews, Kaplan, & Winner (2009), specifically - "empathic call for change". Full Text (PDF)